What makes writing academic: an educational and philosophical response - Molinari, Julia (2019)
This thesis contextualises academic writing in EAP (English for Academic Purposes) and subjects it to an interdisciplinary (educational and philosophical) analysis in order to argue that what makes writing academic are its socio-academic practices and values, not its conventional forms. In rejecting dominant discourses that frame academic writing as a transferable skill which can be reduced to conventional forms, I show that academic writings are varied and evolve alongside changing writer agencies and textual environments. This accounts for the emergence of a diverse academic writing landscape that enacts diverse socio-academic practices and that does not reduce writing to predictable static surface features. My methodology resists traditional disciplinary classifications and is in line with the reflective and interpretative approaches associated with the humanities. Rather than ‘filling a gap’ in academic writing research, I challenge writing conventions in EAP by questioning assumptions. This is because EAP is influential in shaping discourses about academic writing and, as such, it must not mislead students and practitioners about the evolving purposes, forms and possibilities for academic expression. The thesis is divided into three parts, each containing two chapters. Part 1 is concerned with explaining what academic writing is in EAP and how EAP can misrepresent it. Part 2 delves into the history of writing and literacy to tease out the ideologies shaping writing practices. Part 3 proposes a model based on philosophical theories of mind and sociology that lays the foundation for a macro theory of academic writing and a future writing pedagogy. The model re-imagines academic writing as an affordance within a non-linear, emergent and complex social open system. This system can be referred to as an organic unity and requires a shift from conceiving writing as a ‘transferable skill’. When re-imagined as an affordance, change and diversity in academic writing practices become possible.